Bone Remodelling of the Proximal Femur After Hip Revision with a Metaphyseal-Fixation Femoral Stem Component - Li Z; Li M; Yao X; Liu B; Liu S; Liu Z; Zhang B; Han Y (Dove Medical Press, 2023)
Zhijie Li,1,2,* Mengnan Li,1,* Xiaowei Yao,3 Bo Liu,1 Sikai Liu,1 Zeming Liu,1 Binquan Zhang,1 Yongtai Han1 1Department of Osteonecrosis and Hip Surgery, Hebei Medical University Third Affiliated Hospital, Shijiazhuang, People's Republic of China; 2Orthopedics Department, Affiliated Hospital of Hebei Engineering University, Handan, People's Republic of China; 3Orthopedics Department, Hebei Provincial Chest Hospital, Shijiazhuang, People's Republic of China*These authors contributed equally to this workCorrespondence: Yongtai Han, Email yongtaihan@foxmail.comBackground: Whether hip revision with a metaphyseal-fixation femoral stem component can restore the bone mass of the proximal femur remains unclear. The aims of this study were to identify whether the bone mineral density (BMD) of the proximal femur increases following hip revision with a metaphyseal-fixation femoral stem and to identify the factors associated with BMD recovery.Methods: This was a retrospective study involving 36 patients who underwent hip arthroplasty with a metaphyseal-diaphyseal fixation stem (standard length stem) and had indications for hip revision, which was performed with a proximal press-fit short-stem prosthesis for each patient. Dual-energy X-ray absorptiometry (DEXA) was used to obtain, evaluate, and compare the BMD at baseline and one year and two years postoperatively. The proximal femur was divided into several independent areas according to the Gruen zone (Gruen 1 to Gruen 7 from the greater trochanter counterclockwise to the lesser trochanter). Logistic regression analyses were used to assess potential factors significantly associated with an increase in BMD.Results: An increased BMD was obviously identified in the proximal femur. Two years after the surgery, the BMD of the Gruen 1, Gruen 2, Gruen 6, and Gruen 7 areas had increased by 22.6%, 12.6%, 16.2% and 24.2%, respectively, relative to baseline. Three independent risk factors associated with bone mineral density recovery were identified: age (OR=1.100, 95% CI=1.005- 1.203, P=0.038), osteoporosis (OR=14.921, 95% CI=1.223- 182.101, P=0.034) and fair to poor hip function (OR=13.142, 95% CI=1.024- 168.582, P=0.048).Conclusion: This study confirms that metaphyseal-fixation stem hip revision can indeed help restore bone mass in the proximal femur, especially in the Gruen 1, Gruen 2, Gruen 6 and Gruen 7 zones. It was also found that advanced age, osteoporosis, and fair to poor hip joint function were three important risk factors affecting the recovery of proximal femur bone mass after surgery.Trial Registration: Retrospectively registered.Keywords: uncemented fixation, hip revision, bone mineral density, metaphyseal-fixation femoral stem component